Global Existence and Stability in Porous-elasticity with Heat Conduction - Choucha, Abdelbaki (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2022)
The aim of this thesis is to give some results of existence and general decay, as well as providing the reader with the methods used to study some elastic, thermoelastic and viscous systems, as well as some wave equation problems with the presence of various dissipation and damping mechanisms under suitable assumptions. We have used many methods, including: energy method and Lyapunov function. We divided the thesis into three parts: In the first part, we study the existence and general decay of solutions for some porous type systems. As for the second part, we extend the study to other systems, namely Bresse system and Laminate beam. Finally the third part is concerned with wave equation problems including Kirchhoff’s equations, we study general decay, blow-up and growth of solutions with various dissipation and damping mechanisms under suitable conditions. الهدف من هذه الرسالة هو إعطاء بعض نتائج الوجود والإنحلال العام، بالإضافة إلى تزويد القارئ بالطرق المستخدمة لدراسة الأنظمة المرنة، المطاطية الحرارية واللزجة، وكذلك بعض مشاكل معادلة الموجة مع وجود آليات التبديد والتخميد المختلفة في ظل إفتراضات مناسبة. لقد استخدمنا عدة طرق منها : طريقة الطاقة ودالة ليا بونوف. قسمنا الرسالة إلى ثلاثة أجزاء: في الجزء الأول، قمنا بدراسة وجود الحلول لبعض الأنظمة المسامية والإضمحلال العام لها. أما بالنسبة للجزء الثاني، فقد قمنا بتوسيع الدراسة لتشمل أنظمة أخرى، وهي نظام بريس و عارضة مغلفة. أخيرا الجزء الثالث يختص بمشاكل معادلة الموجة بما في ذلك معادلات كيرشوف، نقوم بدراسة الإنحلال العام والتفجير ونمو الحلول بآليات التبديد والتخميد المختلفة في ظل ظروف مناسبة.
أطروحة دكتوراه تخصص رياضيات في العلوم الدقيقة
Keywords: Porous system; Swelling porous system; Stability; General decay; Well-posedness; Delay term; Memory term; Microtemperature damping; Thermoelasticity; Viscoelasticity; Timoshenko system; Bresse system; Laminated beam; Wave equation; Blow-up; Exponential growth.; نظام مسامي؛ تورم نظام مسامي؛ استقرار؛ تسوس عام؛ الوضع الجيد ؛ مصطلح التأخير؛ مصطلح الذاكرة؛ التخميد الدقيق الدرجات الحرارة؛ المرونة الحرارية؛ لزوجة مطاطية؛ نظام تيموشينكو؛ نظام بريس؛ عارضة مغلفة؛ معادلة الموجة؛ تفجير؛ النمو؛ الأسي.